1977
DOI: 10.1099/00221287-101-1-51
|View full text |Cite
|
Sign up to set email alerts
|

The Wall of Rhizobium leguminosarum in Bacteroid and Free-living Forms

Abstract: Walls of the bacteroid form of Rhizobium leguminosarum, from plant nodules, and walls of free-living R. leguminosarum were isolated and compared by extraction with aqueous phenol and chemical analysis. Bacteroid walls had less lipopolysaccharide than walls isolated from bacteria cultured on four different media. This difference may be relevant to the relatively greater permeability of the outer membrane of bacteroids, and important in symbiotic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 25 publications
0
56
0
2
Order By: Relevance
“…Unless otherwise indicated, the ,B-galactosidase values in the tables are expressed as Miller units (21) induced by 30-fold-diluted root exudate and corrected for the background level of the indicator strain, which was 300 to 400 U. Culture supernatant fluids of Rhizobium cells to be tested for the presence of symbiotic signals were taken from cells grown in B medium (39), which, if appropriate, was supplemented with the nod gene inducer naringenin (1 ,uM). The fluids were tested after centrifugation for 10 min' at 6,000 x g and pasteurization for 10 min at 800C.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Unless otherwise indicated, the ,B-galactosidase values in the tables are expressed as Miller units (21) induced by 30-fold-diluted root exudate and corrected for the background level of the indicator strain, which was 300 to 400 U. Culture supernatant fluids of Rhizobium cells to be tested for the presence of symbiotic signals were taken from cells grown in B medium (39), which, if appropriate, was supplemented with the nod gene inducer naringenin (1 ,uM). The fluids were tested after centrifugation for 10 min' at 6,000 x g and pasteurization for 10 min at 800C.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Supernatant fluids of cultures of strain RBL5561 pMP604 in B medium (39) were used as a source of the Ini factor. Heat stability was tested after incubation for 10 min at 1200C.…”
Section: Downloaded Frommentioning
confidence: 99%
“…- [17] при + 28 °C и интенсивном перемешивании 220 об/мин в присутствии 10 мкМ нарингенина (индуктор). Клет-ки осаждали 15 мин при 4000 g, затем супернатант ин-кубировали с бутанолом в течение 1 часа при пере-мешивании 220 об/мин, бутанольную фазу отбирали и выпаривали.…”
Section: материалы и методыunclassified
“…Several reports have indicated that the amount of LPS in the outer membrane decreases in a cell (Van Brussel et al 1977) and that the composition of the membrane changes during the differentiation from free-living bacterium to bacteroid (Brewin et al 1986;Sindhu et al 1990;VandenBosch et al 1989). Goosen-de Roo et al (1991) demonstrated by electron microscopy with monoclonal antibody of O-antigens of LPS of Rhizobium leguminosarum bv.…”
Section: Discussionmentioning
confidence: 99%